Epidemiology of Orofacial Clefts in the East of Ireland in the 25-Year Period 1984–2008. (July 2014) - McDonnell, Robert; Owens, Miriam; Delany, Caroline; Earley, Michael; McGillivary, Anne; Orr, David J.; Duggan, Laura
Objective: To describe the epidemiology of orofacial clefts in the east of Ireland. Design and Setting: A descriptive epidemiologic study on 851 cases of orofacial cleft identified over a 25-year period from 1984 to 2008 from more than 500, 000 births. Results: There were 438 (51.5%) cases of cleft lip with or without cleft palate and 413 (48.5%) cases of cleft palate. The total birth prevalence was 16.0 per 10, 000 births for all orofacial clefts, 8.2 for cleft lip with or without cleft palate, and 7.8 for cleft palate. Of all cases, 63.7% (542/851) occurred as isolated anomalies, 21.5% (183/851) were associated with multiple anomalies, and 14.8% (126/851) were associated with a syndrome or chromosomal anomaly. A significantly increasing trend over the 25-year period was observed for cleft lip with or without cleft palate associated with syndromes or chromosomal anomalies among mothers younger than 35 years but not in those older than 35 years. Conclusion: A slightly higher rate of orofacial clefts was observed in the east of Ireland than was observed in European and multinational studies during the study period, and there were higher rates of cleft palate. The rising trend in the proportion of mothers aged 35 years or older in Ireland is not contributing significantly to orofacial clefts associated with chromosomal syndromes.